Binimetinib inhibits MEK and is effective against neuroblastoma tumor cells with low NF1 expression. Issue 1 (December 2016) - Woodfield, Sarah; Zhang, Linna; Scorsone, Kathleen; Liu, Yin; Zage, Peter
Abstract Background Novel therapies are needed for children with high-risk and relapsed neuroblastoma. We hypothesized that MAPK/ERK kinase (MEK) inhibition with the novel MEK1/2 inhibitor binimetinib would be effective in neuroblastoma preclinical models. Methods Levels of total and phosphorylated MEK and extracellular signal-regulated kinase (ERK) were examined in primary neuroblastoma tumor samples and in neuroblastoma cell lines by Western blot. A panel of established neuroblastoma tumor cell lines was treated with increasing concentrations of binimetinib, and their viability was determined using MTT assays. Western blot analyses were performed to examine changes in total and phosphorylated MEK and ERK and to measure apoptosis in neuroblastoma tumor cells after binimetinib treatment. NF1 protein levels in neuroblastoma cell lines were determined using Western blot assays. Gene expression ofNF1 andMEK1 was examined in relationship to neuroblastoma patient outcomes. Results Both primary neuroblastoma tumor samples and cell lines showed detectable levels of total and phosphorylated MEK and ERK. IC50 values for cells sensitive to binimetinib ranged from 8 nM to 1.16 μM, while resistant cells did not demonstrate any significant reduction in cell viability with doses exceeding 15 μM. Sensitive cells showed higher endogenous expression of phosphorylated MEK and ERK. Gene expression ofNF1, but notMEK1, correlated with patient outcomes in neuroblastoma, and NF1 protein expression also correlated with responses to binimetinib. Conclusions Neuroblastoma tumor cells show a range of sensitivities to the novel MEK inhibitor binimetinib. In response to binimetinib, sensitive cells demonstrated complete loss of phosphorylated ERK, while resistant cells demonstrated either incomplete loss of ERK phosphorylation or minimal effects on MEK phosphorylation, suggesting alternative mechanisms of resistance. NF1 protein expression correlated with responses to binimetinib, supporting the use of NF1 as a biomarker to identify patients that may respond to MEK inhibition. MEK inhibition therefore represents a potential new therapeutic strategy for neuroblastoma.